2018
DOI: 10.1016/j.biomaterials.2018.02.047
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell derived phenotypic human neuromuscular junction model for dose response evaluation of therapeutics

Abstract: There are currently no functional neuromuscular junction (hNMJ) systems composed of human cells that could be used for drug evaluations or toxicity testing in vitro. These systems are needed to evaluate NMJs for diseases such as amyotrophic lateral sclerosis, spinal muscular atrophy or other neurodegenerative diseases or injury states. There are certainly no model systems, animal or human, that allows for isolated treatment of motoneurons or muscle capable of generating dose response curves to evaluate pharmac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
132
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(139 citation statements)
references
References 53 publications
0
132
0
Order By: Relevance
“…Alternatively, given that we did not observe bona fide Schwann cells in our co-culture, the addition of independently derived Schwann cells may stabilize the co-culture for longer-term studies and enable further NMJ maturation. Although sKM displayed hypertrophy during co-culture, use of bioengineering strategies such as compartmentalized microfluidic devices or nano-patterned hydrogels may also provide a more native environment for each respective cell type, leading to stable, long-term co-cultures (Ionescu et al, 2016;Langhammer et al, 2012;Santhanam et al, 2018;Uzel et al, 2016;Zahavi et al, 2015, Osaki et al, 2018.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, given that we did not observe bona fide Schwann cells in our co-culture, the addition of independently derived Schwann cells may stabilize the co-culture for longer-term studies and enable further NMJ maturation. Although sKM displayed hypertrophy during co-culture, use of bioengineering strategies such as compartmentalized microfluidic devices or nano-patterned hydrogels may also provide a more native environment for each respective cell type, leading to stable, long-term co-cultures (Ionescu et al, 2016;Langhammer et al, 2012;Santhanam et al, 2018;Uzel et al, 2016;Zahavi et al, 2015, Osaki et al, 2018.…”
Section: Discussionmentioning
confidence: 99%
“…Advances in hiPSC differentiation have shown formation of functional NMJs in vitro between hiPSC-MN and rodent sKM (Umbach et al, 2012;Yoshida et al, 2015), and between hiPSC-MNs and primary human sKM (Santhanam et al, 2018;Steinbeck et al, 2015;Afshar Bakooshli et al, 2019) or hiPSC-sKM (Puttonen et al, 2015, Osaki et al, 2018, Osaki et al, 2020 . Recent demonstrations have shown that 3D neuromesodermal organoids can generate functional NMJs that consist of sKM, MNs, and Schwann cells (Faustino Martins et al, 2020) .…”
Section: Introductionmentioning
confidence: 99%
“…Copyright 2010, Elsevier Ltd. c) Engineering the neuromuscular junction (NMJ) using a microchip: The microchip allowed the coculture of separate populations of motor neurons and human skeletal myoblasts connected through microchannels. Adapted with permission . Copyright 2018, Elsevier Ltd. d) Coculture of muscle and embryonic bodies (EBs) of differentiated motor neurons on 3D printed hydrogel mold.…”
Section: Skeletal Muscle Tissue Engineeringmentioning
confidence: 99%
“…To address the need for a sensitive, human‐based functional NMJ model with segregated readouts, a high‐content phenotypic NMJ system was developed by integrating the biological system with a BioMEMs construct which allows repetitive temporal interrogation of NMJ function and relevant drug testing in a separated platform. [ 21 ] In the current study, ALS patient iPSC‐derived MNs were combined with this BioMEMs engineered NMJ system to develop a defined functional neuromuscular system to study NMJ function of different ALS phenotypes and their chronological changes. The function of the established NMJs was characterized and clinically relevant phenotypes were identified from these ALS‐NMJs and correspondent parameters have been defined for this ALS‐NMJ model system.…”
Section: Introductionmentioning
confidence: 99%